Predicting the future climate-related prevalence and distribution of crop pests and diseases affecting major food crops in Zambia - Nguru, Wilson; Mwongera, Caroline (2023)
Environmental factors determine the suitability of natural habitats for crop pests and often facilitate their proliferation and that of the crop diseases they carry. Crop pests and diseases damage food crops, significantly reducing yields for these commodities and threatening food security in developing, predominantly agricultural economies. Given its impact on environmental factors, climate change is an important determinant of crop pest and disease distribution. This study uses Targeting Tools, a climate suitability analysis and mapping toolkit, to explore the potential impact of climate change on select environmental factors linked to crop pest and associated diseases’ proliferation. Based on the existing literature, prediction modeling was performed on 21 key pests and diseases that impact the major food crops for Zambian consumption. Future changes in habitat suitability for these crop pests and diseases were mapped based on their optimal temperature and relative humidity conditions for proliferation. Results project that there will be an overall increased geographical spread of suitable habitats for crop pests (and as follows, crop diseases) that thrive in warmer environments. By the 2030s, crop pests and diseases will increasingly spread across Zambia, with a higher likelihood of occurrence projected under RCPs 2.6, 4.5, and 8.5. Crop pests and diseases that thrive in cooler environments will experience decreasing habitat suitability in the 2030s, but will transition to a slower decrease in the 2050s under RCPs 2.6 and 4.5. Overall crop pest and disease habitat suitability will continue to rise slowly in the 2050s; RCP 8.5 shows an increased habitat suitability for crop pests and diseases that thrive in warm environments, with a decreased likelihood of occurrence for crop pests and diseases that thrive in cooler environments. The results highlight the need for future-facing, long-term climate adaptation and mitigation measures that create less suitable microclimates for crop pests and diseases.